2003
DOI: 10.1007/s00270-002-2647-9
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Placement of Metallic Stents in Malignant Biliary Obstruction: One-Stage or Two-Stage Procedure? Pre-Dilate or Not?

Abstract: The aim of this paper was to evaluate the necessity of percutaneous transhepatic catheter drainage and balloon dilation procedures performed before stent insertion. One hundred and twenty-six patients with unresectable malignant biliary obstruction underwent palliative therapy by means of percutaneous transhepatic placement of 183 metallic biliary endoprotheses. Forty-four (35%) patients underwent metallic stent insertion in a one-stage procedure and 82 (65%) had undergone percutaneous transhepatic catheter dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…There are detailed guidelines and many reports on the techniques, indications, complications and management of malignant biliary obstructions. However, to our knowledge, the factors that may affect the ability of a malignant biliary obstruction to be crossed have not been discussed in detail in the existing literature (1)(2)(3)(4)(5)(6)(7)(8). In the studies of Neal et al (9) and Dowsett et al (10), the ability of biliary strictures to be traversed was found to be unrelated to stricture type or location.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There are detailed guidelines and many reports on the techniques, indications, complications and management of malignant biliary obstructions. However, to our knowledge, the factors that may affect the ability of a malignant biliary obstruction to be crossed have not been discussed in detail in the existing literature (1)(2)(3)(4)(5)(6)(7)(8). In the studies of Neal et al (9) and Dowsett et al (10), the ability of biliary strictures to be traversed was found to be unrelated to stricture type or location.…”
Section: Discussionmentioning
confidence: 93%
“…In patients with a high-level obstruction and in patients with low-level obstruction for whom endoscopic intervention is not suitable, the percutaneous transhepatic approach is the palliative treatment of choice. Indications, technical procedures, related complications, and success rates of percutaneous intervention have been discussed in detail in previous studies (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Currently, both protocols are utilized side by side at many institutions as patient-related factors, which may determine the complication rate and outcome, are not well defined. [8]…”
Section: Introductionmentioning
confidence: 99%
“…В на-стоящее время лишь небольшое количество паци-ентов с опухолями панкреатодуоденальной зоны могут быть оперированы радикально, большин-ству же возможно выполнить лишь паллиативное лечение [20][21][22], при этом в большинстве случаев используются обходные анастомозы или стентиро-вание, в том числе в сочетании с химио-, радио-, фотодинамической терапией, химиоэмболизацией [23][24][25][26][27][28][29].…”
unclassified